Edge Effects along a Seagrass Margin Result in an Increased Grazing Risk on Posidonia australis Transplants. - Statton, J.; Gustin-Craig, S.; Dixon, Kingsley; Kendrick, G. (Public Library of Science, 2015)
A key issue in habitat restoration are the changes in ecological processes that occur when fragments of habitat are lost, resulting in the persistence of habitat-degraded margins. Margins often create or enhance opportunities for negative plant-herbivore interactions, preventing natural or assisted re-establishment of native vegetation into the degraded area. However, at some distance from the habitat margin these negative interactions may relax. Here, we posit that the intensity of species interactions in a fragmented Posidonia australis seagrass meadow may be spatially dependent on proximity to the seagrass habitat edge, whereby the risk of grazing is high and the probability of survival of seagrass transplants is low. To test this, transplants were planted 2 m within the meadow, on the meadow edge at 0m, and at 2m, 10m, 30m, 50m and 100m distance from the edge of the seagrass meadow into the unvegetated sand sheet. There was an enhanced grazing risk 0-10m from the edge, but decreased sharply with increasing distances (>30m). Yet, the risk of grazing was minimal inside the seagrass meadow, indicating that grazers may use the seagrass meadow for refuge but are not actively grazing within it. The relationship between short-term herbivory risk and long-term survival was not straightforward, suggesting that other environmental filters are also affecting survival of P. australis transplants within the study area. We found that daily probability of herbivory was predictable and operating over a small spatial scale at the edge of a large, intact seagrass meadow. These findings highlight the risk from herbivory can be high, and a potential contributing factor to seagrass establishment in restoration programs.